DOI: 10.11606/d.100.2018.tde-12122018-225451
|View full text |Cite
|
Sign up to set email alerts
|

Hospitais de alta complexidade do Estado de São Paulo: comparação entre administração direta e gestão por organizações sociais

Abstract: TONELOTTO, Diego Pugliese. Hospitals of high complexity in the State of São Paulo: comparison between direct administration and management by social organizations. 2018. 126p. Dissertation (Master of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Miscellaneous published studies demonstrated that public state hospitals in São Paulo managed by OSS produced much more and with higher quality than the corresponding units under direct administration with the same budget, thus more efficiently [5][6][7][8][9][10][11] . Only one study 12 showed that hospitals under direct administration displayed lower costs, but it featured several biases in the determination of costs and it did not account for quantitative and qualitative production indicators, which compromised results and conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Miscellaneous published studies demonstrated that public state hospitals in São Paulo managed by OSS produced much more and with higher quality than the corresponding units under direct administration with the same budget, thus more efficiently [5][6][7][8][9][10][11] . Only one study 12 showed that hospitals under direct administration displayed lower costs, but it featured several biases in the determination of costs and it did not account for quantitative and qualitative production indicators, which compromised results and conclusions.…”
Section: Introductionmentioning
confidence: 99%